REPRODUCTIVE BIOLOGY OF FIVE SPECIES OF ANCHOVIES (ENGRAULIDAE) FROM BIMA BAY, SUMBAWA, NUSA TENGGARA - Retno Andamari; David Milton; Thohir Zubaidi (Indonesian Agency for Agricultural Research and Development, 2002)
The reproductive biology of five species of anchovies (Encrasicholina and Stolephorus) in Bima Bay, Nusa Tenggara, Indonesia was examined and compared with previous studies of the same species in Bacan, Maluku and other parts of Indonesia. Fish and plankton sampling was conducted in February and April 2000. The length and weight relationship of five species of anchovies had a slope (b) that ranged from 2.71 to 3.74. These values were less than those found in Bacan for the same species. All species were multiple spawner and the mean batch fecundity ranged between 1226 (Encrasicholina devisi) and 2470 (E. punctifer). Relative fecundity varied among the species inversely with size, being lower in the larger species. Age at first spawning varied from 67 to 141 days for all five species and was higher in Stolephorus species. Lifetime egg production was less than that found in Bacan for the same species, but similar to that found in similar habitats elsewhere in the tropical Indo-Pacific. These results suggest that anchovy egg production is higher, but more variable in open oceanic environments compared with the more stable, coastal bays.